Journal of Empowerment Management of Disaster Preparedness School in Preparing the Students to Care About the Environment in the Public Senior High Schools in the Special Capital Region of Jakarta - Yani Ganefiyanto; Iim Wasliman; Sofyan Sauri; Cahya Syaodih (Journal of Islamicate Studies, 2022)
The empowerment of disaster preparedness so far has not been able to answer the community's needs and demands about high school graduates who care about the environment. The obstacles of this research were that human educational resources have not been competent, so they need to be empowered. This research used descriptive methods and techniques of observation, interviews, and documentation. This study examined how disaster preparedness school empowerment in preparing students to care about the environment at Public Senior High Schools in Jakarta positively impacted students' environmental care behavior. It used a qualitative approach, following the philosophy of constructivism. The research subjects were headmaster principals, teachers, administrative staff, school committees, and parents. Some obstacles included budget or finance, infrastructure, and environmental demands of areas prone to disasters.